Compliance of Hazard Analysis and Critical Control Point (HACCP) in Accordance to MS 1480:2007 at Blue Sky Bird Nest Sdn Bhd /Amin Zairi Abdul Fatah... [et al.] - Abdul Fatah, Amin Zairi; Laing, Rude; Asoon, Herojer (2014)
The purpose of this study is to investigate whether Blue Sky Bird’s Nest (BSBN) complies with the Hazard Analysis and Critical Control Point (HACCP) requirement in accordance to MS 1480:2007 in regards to its process flow and the physical condition of the processing plant. In addition to this, this study will also identify the difficulties faced by the company in taking steps in complying with the standard. The third and last objective of this study is to give recommendations to the company on the issues that needs to be rectified in order to minimize the level of unconformity of the processing plant to the standards of HACCP. The investigation was made by conducting interviews and gathering information on various journals regarding HACCP, but most of the information is gathered by observation on the processing plant itself and examining the documents of the company. From the study, it is found that BSBN had complied with 89% of the physical aspect of the plant and 95% of its technical aspects which includes the process flow of processing the product. The conclusion for this study found that BSBN is on the right track to obtain HACCP certificate with some minor improvements needs to be made. Thus, the owner’s target in obtaining the HACCP certificate by early 2015 is most likely to be achieved.